ULOGA PREDUZETNIŠTVA I SPORTSKOG MENADŽMENTA U RAZVOJU KLUPSKOG PROFESIONALNOG SPORTA - Ljubivoje Mladenović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Development of professional sport experienced the important transformation in the last fifty years. The key factors of transformation were involvement of entrepreneur, business people and individual investitures in sport. In this period sport became extraordinary attractive per direct and indirect audience with help broadcasting. This attracted lot of investitures and sponsors not just in order of making profit but also in order of personal promotion. Professional sport and investitures were joined and made great business and one of the most development industry in the world, sport industry. All of these contributed faster development professional sport specially in North America and Europe in the most attractive sport area: football, basketball, tennis, athletic etc. That attracted lot of investitures and sponsors not just in order to make a profit but also in order with there personal media promotions. This trend expanded and area of Former Yugoslavia, and today of Serbia and Montenegro, with specific limits and exceptions